Learning through the screen: Malaysian parents’ perspectives on youtube and their children’s english acquisition - Mohamat Kusin, Maizatul Kasmadiana; Mohamed Salleh, Rabiah Tul Adawiyah (Southeast Asia Early Childhood Journal, 2025)
YouTube is a widely used digital platform that plays a significant role in children’s daily exposure to digital content. Despite its popularity, there is limited research on YouTube’s specific influence on young children’s English language acquisition in non-Western contexts like Malaysia, where English is not the first language. Existing studies often focus on general screen time, leaving a gap in understanding YouTube’s specific role in shaping early language learning. This study addresses this gap by exploring Malaysian parents’ perceptions of YouTube’s impact on their children’s English language development. Using qualitative methods, interviews were conducted with ten parents of children aged five to six who use YouTube. Thematic analysis revealed five key themes: the duration of YouTube access, children’s improvement in English skills, the types of content consumed, YouTube’s effectiveness as a learning platform, and the role of parental supervision. Parents noted that English cartoons, nursery rhymes, and storytelling videos enhanced their children’s speaking abilities, vocabulary acquisition, listening comprehension, and spelling skills. While parents valued YouTube’s accessibility and variety, they raised concerns about inappropriate content and stressed the importance of parental supervision. Monitoring emerged as a crucial parental strategy, with parents actively selecting suitable content and setting clear boundaries to support their children’s education and uphold cultural values.